Beyond Birthweight: The Origins of Human Capital - Gabriella Conti; Mark Hanson; Hazel Inskip; Sarah Crozier; Cyrus Cooper; Keith Godfrey (Institute of Labor Economics (IZA), 2020)
Birth weight is the most widely used indicator of neonatal health, mainly because it is routinely recorded in birth registries. But are better measures available? We use unique data including fetal ultrasounds to show that more specific measures of the fetus and of the newborn are more informative about the prenatal environment and more predictive of child health and development, beyond birth weight. Our results are robust to correcting for measurement error and accounting for child- and mother-specific unobserved heterogeneity. Our analysis rationalizes a common finding in the early origins literature, that prenatal events can influence postnatal development without aecting birth outcomes.
Keywords: I12; J13; J24; 330; birth weight; fetal development; child health; developmental origins; measurement